Analgesic Efficacy of α2 Adrenergic Receptor Agonists Depends on the Chronic State of Neuropathic Pain: Role of Regulator of G Protein Signaling 4. (10th February 2021) - Yoon, Seo-Yeon; Roh, Dae-Hyun; Yeo, Ji-Hee; Woo, Jiwan; Han, Se Hee; Kim, Key-Sun
Highlights: Analgesic effect of α2 AR agonists is attenuated over time after spared nerve injury. Plasma membrane RGS4 levels are increased in chronic state of neuropathic pain. Decreased analgesic effect of α2 AR agonists is restored by the inhibition of RGS4. Abstract: The analgesic effect of alpha-2 adrenergic receptor (α2 AR) agonists, which relieve chronic neuropathic pain, is highly variable among individuals. Here, we used a mouse model of spared nerve injury (SNI) to show that treatment time after the establishment of neuropathic pain was important for the variability in the analgesic efficacy of α2 AR agonists, which was related to the activity of regulator of G-protein signaling protein 4 (RGS4). Intrathecal treatment with α2 AR agonists, clonidine (0.1–1 nmol) or dexmedetomidine (0.3–1 nmol), relieved mechanical allodynia and thermal hyperalgesia on postoperative day (POD) 14, but their efficacy was weaker on POD28 and absent on POD56. The RGS4 level of plasma membrane was increased on POD56 compared to that on POD14. Moreover, in RGS4-deficient or RGS4 inhibitor (CCG50014)-treated mice, the analgesic effect of the α2 AR agonists was conserved even on POD56. The increased plasma membrane RGS4 expression and the reduced level of active Gαi after clonidine injection on POD56 were completely restored by CCG50014. Higher doses of clonidine (10 nmol) and dexmedetomidine (3 nmol) relieved neuropathic pain on POD56 but were accompanied with serious side effects. Whereas, the coadministration of CCG50014 with clonidine (1 nmol) or dexmedetomidine (1 nmol) did not cause side effects. These findings demonstrated that SNI-induced increase in plasma membrane RGS4 expression was associated with low efficacy of α2 AR agonists in a model of persistent, chronic neuropathic pain. Furthermore, α2 AR agonist administration together with RGS4-targeted intervention represents a novel strategy for the treatment of neuropathic pain to overcome dose-limiting side effects.